Relationships among perceived stress, anxiety, and well-being in Chinese hospital staff: the mediating role of self-efficacy and the moderating role of empathy - Li, Mingji; Yang, Guohai; Xu, Xianhua; Oh, Insoo; Xu, Shijie (Frontiers in Psychology, 2026)
ObjectiveThis study aimed to investigate whether self-efficacy mediates the relationship between perceived stress/anxiety and well-being and whether empathy moderates the association between self-efficacy and well-being.MethodsA cross-sectional study was conducted among 543 full-time hospital staff members at Hainan Cancer Hospital in China. Participants completed the Perceived Stress Scale (PSS-10), the Generalized Anxiety Disorder Scale (GAD-7), the General Self-Efficacy Scale (GSES), the Interpersonal Reactivity Index (IRI), and the WHO-5 Well-being Index. A moderated mediation analysis was performed using the SPSS PROCESS Macro.ResultsMediation analysis indicated that self-efficacy partially mediated the relationship between perceived stress/anxiety and well-being. Empathy moderated the relationship between self-efficacy and well-being, enhancing its protective effects. Specifically, individuals with higher levels of empathy exhibited a stronger positive association between self-efficacy and well-being, highlighting the synergistic role of empathy in mitigating the adverse effects of stress and anxiety.ConclusionThese findings underscore the importance of interventions targeting self-efficacy and empathy to improve well-being among hospital staff. This study contributes to the growing body of literature on occupational mental health in high-stress healthcare settings.